TINDAK TUTUR ILOKUSI DALAM KOMENTAR WARGANET TERHADAP UNGGAHAN VIDEO KINERJA JOKOWI PADA AKUN CNN INDONESIA DI MEDIA SOSIAL TIKTOK - Nur Rohmah, Zunita Anggreni; Dwi Rahmayantis, Marista; Lailiyah, Nur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The aim of this study is to describe the forms and functions of illocutionary speech acts in netizens’ comments on a video of Jokowi’s performance posted on the CNN Indonesia account on the social media platform TikTok. A pragmatic approach was employed in this study. This is a qualitative study. The forms of speech acts were analysed using Searle’s theory (1979) and Leech’s functions (2016). The data source consisted of TikTok comments. The observation and note-taking technique was used in this study. The findings were categorised into five forms of illocutionary speech acts: assertive (17), directive (2), commissive (22), expressive (75), and declarative (0), with a total of 117 data points, and illocutionary function categories: competitive (0), convivial (26), collaborative (6), and conflictive (0), with a total of 32 data points. The category with the most data was the expressive category (75), and the one with the least was the directive category (2). The category with the most data in terms of function was the convivial category (26), and the one with the least was the collaborative category (6).